Paperless Arabic Language Learning: Integrating Ecotheology, Bilingual Education, and the Love-Based Curriculum in Madrasah - Ifkar Rasyid; Zaimatuz Zakiyah; Sri Indah Lestari; Ikysarul Akhyari (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Background: Deforestation and rising carbon emissions resulting from excessive paper use in education have encouraged the development of sustainable, technology-based, and environmentally friendly learning models. Research Objectives: This study aims to describe the implementation of paperless bilingual learning in Arabic at MTs Quranic Scientia, UIN Imam Bonjol Padang, analyze its alignment with eco-theological principles; examine the role of the Love-Based Curriculum (KBC); and identify its opportunities and challenges in supporting Arabic learning. Methodology: This study employed a qualitative approach with an instrinsic case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving teachers, students, and school administrators. To ensure validity, the study applied triangulation and member checking, while data were analyzed iteratively through data reduction, display, and conclusion drawing. Results:. The findings reveal that paperless bilingual Arabic learning supported by iPads, smartboards, and the Cerdig e-learning platform enhances students’ Arabic proficiency, digital literacy, and classroom engagement. The integration of the Love-Based Curriculum fosters collaborative, caring, and confidence-building learning interaction, while ecotheological values strengthen students’ environmental awareness and responsibility. Despite challenges related to language proficiency, technical issues, and students’ self-confidence, the model demonstrates significant potential in promoting sustainable, technology-based Islamic education. Unique Contribution: The integration of the Love-Based Curriculum strengthens values of environmental responsibility, compassion, and respect within the learning process, offering an integrative model combining paperless learning, bilingual education, and eco-theological in Islamic education. Conclusion: This study concludes that the approach improves students’ Arabic proficiency, academic performance, and digital skills while fostering ecological awareness. Recommendations: This model is recommended for adaptation in other madrasahs with contextual adjustments.